A Review on Sustainable Eco-friendly Cutting Fluids - Deshpande, Viraja; Jyothi, P N (Journal of Sustainability and Environmental Management, 2022)
In machining industries, cutting fluids plays a vital role as they are used to improve machinability and to have better productivity. Using mineral oil as cutting fluids has a negative impact on environment and also on the operator’s health as it is non-bio-degradable and hazardous. Research work is been carried out for replacing these mineral oils by bio- degradable oils. The few vegetable oils possess characteristics of good cutting fluids such as viscosity, heat absorption capacity, fatty acid chains, biodegradability, non-toxicity etc. This paper reviewed research works carried out on different types of eco-friendly oils used as cutting fluids for different machining operations and on different materials. The effects of using different vegetable oils as cutting fluids on machining parameters have been discussed. From the results, it was observed that, the bio-oils possesses properties of  good cutting fluids and has shown better results in terms of  improving machining efficiency  when compared to mineral or petroleum oils. These bio-oils possess better sustainability and biodegradability. Hence also called as eco-friendly cutting fluids. There is more scope for modification of bio-oils by having some additives and nano particles to have improved lubricating properties.